Beyond a middle income Africa: Transforming African economies for sustained growth with rising employment and incomes: Executive summary - Badiane, Ousmane; Makombe, Tsitsi (International Food Policy Research Institute, 2015)
The 2014 Annual Trends and Outlook Report examines both current and future trends that are likely to shape the trajectory of African economies. The report examines the drivers behind the recent growth recovery, the nature and patterns of structural transformation among African economies, past strategies and future outlook for industrialization, the changes occurring in agrifood systems, and the role of major infrastructure sectors in the continent’s past and future growth. The report also analyzes major global- and continental-level trends that may shape future growth across the continent and affect the region’s integration into global value chains.